2018
DOI: 10.1182/bloodadvances.2017009654
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of idiopathic multicentric and unicentric Castleman disease and follicular dendritic cell sarcomas

Abstract: Castleman disease (CD) is a rare lymphoproliferative disorder subclassified as unicentric CD (UCD) or multicentric CD (MCD) based on clinical features and the distribution of enlarged lymph nodes with characteristic histopathology. MCD can be further subtyped based on human herpes virus 8 (HHV8) infection into HHV8-associated MCD, HHV8/idiopathic MCD (iMCD), and polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin change (POEMS)-associated MCD. In a subset of cases of UCD, an associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…To date, histological examination remains the primary method of sarcoma diagnosis ( 36 ). The histological and molecular heterogeneity of sarcoma make it particularly difficult to diagnose, though with the rapid development of NGS technology, increasing numbers of sarcoma genome sequencing studies have emerged ( 37 40 ). In the present study, the most commonly mutated genes were identified in 199 patients with sarcoma, and included TP53, CDKN2A, CDKN2B, KIT, ATRX and RB1 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, histological examination remains the primary method of sarcoma diagnosis ( 36 ). The histological and molecular heterogeneity of sarcoma make it particularly difficult to diagnose, though with the rapid development of NGS technology, increasing numbers of sarcoma genome sequencing studies have emerged ( 37 40 ). In the present study, the most commonly mutated genes were identified in 199 patients with sarcoma, and included TP53, CDKN2A, CDKN2B, KIT, ATRX and RB1 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers assumed that FDC sarcoma arose from hyaline vascular Castleman disease, possibly through a mechanism involving epidermal growth factor receptors[ 37 ]. A recent genetic study has suggested that FDC sarcomas associated with unicentric hyaline-vascular Castleman disease show mutations and copy number changes in known oncogenes, tumor suppressors, and chromatin remodeling genes[ 38 ]. In addition, histologically, indolent T-lymphoblastic proliferation is frequently found in FDC sarcomas and shows an association with paraneoplastic autoimmune multiorgan syndrome; this association suggests that neoplastic follicular dendritic cells can recruit or foster the proliferation of immature T cells, which may lead to the occurrence of PNP[ 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data above identify pathogenic genetic variants in two out of three subjects studied with iMCD-TAFRO. Although, a DNMT3A mutation was previously reported in an iMCD-TAFRO patient [ 11 ], the causative relationship of this mutation to iMCD-TAFRO is uncertain as DNMT3A is frequently mutated in clonal hematopoiesis [ 12 , 13 ]. Another study reported a germline FASL mutation in a family with unicentric Castleman disease and iMCD [ 14 ].…”
Section: Resultsmentioning
confidence: 99%